Impact of motor symptom asymmetry on non-motor outcomes in Parkinson’s disease: a systematic review - P. Voruz; D. Guérin; J. A. Péron (npj Parkinson's Disease)
Abstract Parkinson’s disease (PD) presents with diverse symptoms, partly influenced by motor symptom asymmetry, which reflects hemispheric brain specialization. This systematic review of 80 studies explored how lateralized motor symptoms affect non-motor outcomes in PD, including cognition, emotion, and psychiatric health. Patients with right-sided motor symptoms (left-hemisphere pathology) show more global cognitive decline and higher dementia risk, while those with left-sided symptoms (right-hemisphere pathology) more often experience psychiatric issues like depression, anxiety, and impaired emotional recognition. Visuospatial deficits were consistently linked to left-sided symptoms, aligning with right-hemisphere dysfunction. Although findings vary across studies, this pattern suggests the relevance of brain lateralization in non-motor symptom assessment. Motor asymmetry may also affect treatment responses, such as deep brain stimulation outcomes. However, inconsistencies in study methods—definitions of asymmetry, motor subtypes, and comorbidities—limit meta-analytic conclusions. Overall, incorporating motor symptom asymmetry into PD diagnosis and treatment could enhance personalized care, warranting more standardized future research.